Neurocognitive Profiles in Childhood Absence Epilepsy: A Focus on Cognitive Dysfunction Associated With the Frontal Lobe. (January 2017) - Cheng, Dazhi; Yan, Xiuxian; Gao, Zhijie; Xu, Keming; Zhou, Xinlin; Chen, Qian
Although neuropsychological studies have demonstrated specific cognitive impairments in children with childhood absence epilepsy (CAE), the potential role of the frontal lobe in these cognitive deficits remains unclear. We therefore evaluated cognitive functions related to and unrelated to the functionality of the frontal lobe in childhood absence epilepsy patients and control subjects. Thirty-seven childhood absence epilepsy patients and 37 age- and gender-matched healthy control subjects were recruited and assessed using a computerized neuropsychological test battery. Childhood absence epilepsy patients, especially a drug-naïve subgroup, showed cognitive deficits in reasoning, visual attention, and executive function, which are typical cognitive functions of the frontal lobe. In contrast, treated childhood absence epilepsy patients only exhibited cognitive deficits in visual attention. There were no significant between-group differences for other cognitive tests. Our findings suggest that frontal lobe–related cognitive deficits represent the characteristic neuropsychological profile associated with childhood absence epilepsy.